Identifikasi Karakteristik Furnitur Di Balai Kota Banda Aceh (Studi Kasus: Gedung A Mawardy Nurdin) - M Fauzia; S M Hasan; D Andriani (Cered Indonesia Institute, 2026)
This study identifies the characteristics of furniture in the Mawardy Nurdin Building A, Banda Aceh City Hall, and analyzes its compliance with Banda Aceh Mayoral Regulation No. 32 of 2017. Using a descriptive qualitative approach, the study was conducted in workspaces on floors 1–3 through observation, documentation, and literature review. The results indicate that while the type and quantity of furniture are generally adequate, there are significant discrepancies in the dimensions, models, and materials of furniture compared to standards, potentially impacting comfort, ergonomics, and work productivity. These findings recommend the need for regular audits, adjustments to furniture procurement, and increased attention to ergonomic aspects in the management of government work facilities.